A importância da literatura infantil afro-brasileira e africana no ensino fundamental do SESC - Petrolina/PE - Aurilia de Brito Lima; Fabiana Cristina da Silva (Universidade do Estado do Rio Grande do Norte, 2013)
This article aims to analyze the use and the repercussions that occurred with the children's literature Afro-Brazilian and African elementary education of SESC-Petrolina. It was used as the theoretical authors and documents as Brazil (2003), Coelho (2002), Jovino (2006) among others. As methodological resources, documentary analysis took place (the acquis of the SESC), observation of classrooms from 1st to 5th year of elementary school and questionnaires applied through the pedagogical coordinator, librarian and teachers of their respective classes. Found a small, but representative writings about qualitative thematic Afro-Brazilian and African noting that, despite the fact that teachers have the knowledge about the legislation and the theme, the actions taken are not systematized. It is believed in the importance of children's literature and other didactic instruments in promoting and recoverability of a portion of the population historically excluded. As a democratic education, with new paradigms of education valuing the culture diversity and ensuring compliance with the Afro-Brazilian and African culture.